Unveiling the nexus between minimum dietary diversity and anemia among children aged 6–23 months in India: evidence from NFHS-5 (2019–2021) - Koyel Majumder; Mithun Sarkar; Rahul Mallick; Bikash Barman; Pradip Chouhan (Cogent Social Sciences)
The target 3.2 of Sustainable Development Goals is to put an end to all preventable newborn and child deaths under the age of 5 by 2030, and the prevalence of anemia (hemoglobin level in blood <11 g/dL) among children is a serious health concern in developing nations, such as India. As minimum dietary diversity (MDD) is significantly associated with hemoglobin status in children, the current study seeks to identify the association between MDD and anemia among children aged 6–23 months in India based on the latest dataset of the National Family Health Survey (NFHS-5) conducted during 2019–2021. A total of 58,345 mother-child pairs of children (aged 6–23 months) and 15–49 years mothers were included in this study. Bivariate statistics and multivariable logistic regression analyses were performed to determine the association between MDD and anemia among children in India. It was found that over 79.02% of children aged 6–23 months had anemia. According to the results, children who consumed MDD had a notably lower risk of anemia (Adjusted Odds Ratio = 0.913; 95% Confidence Interval 0.870–0.959; p < .05). Therefore, the study findings suggest that the government should place greater emphasis on resolving the MDD inadequacies among children to eliminate the burden of anemia in India.